2018
DOI: 10.5897/ajar2017.12949
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lime, vermicompost and chemical P fertilizer on yield of maize in Ebantu District, Western highlands of Ethiopia

Abstract: ) and harvest index (24%) were obtained at 2.5 t ha -1 VC and 40 kg P ha -1 with lime. Integrated application of organic and chemical fertilizers with lime amended the acidic soils and improved its fertility which in turn increased crop yields. Combined use of VC at 2.5 t ha -1 and chemical P fertilizer at 20 kg ha -1 with lime at 4 t ha -1 is economically optimum and could be recommended for reclaiming soil acidity and improve nutrients for maize as it enhanced grain yield and yield components of maize plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
5
8
0
Order By: Relevance
“…Afe, Atanda, Aduloju, Ogundare, and Talabi ( 2015) also reported that plots treated with combined application of poultry manure (2.5 t ha −1 ) mixed with 30 kg N ha −1 and foliar fertilizer commenced tasselling earlier at 38 days after planting while late (47 days) tasselling was recorded from the control. The above finding was in harmony with Bekele, Kibret, Bedadi, Balemi, and Yli-Halla (2018) who reported, the combined application of vermicompost, mineral P and lime significantly speeded up tasseling of maize. Early (102) days to tasseling were recorded with the application of lime, vermicompost, and mineral P fertilizer at the rate of 4 t ha −1 , 5 t ha −1 , and 40 kg ha −1 , respectively.…”
Section: Phenological Parameters Days To 50% Tasselingsupporting
confidence: 87%
See 2 more Smart Citations
“…Afe, Atanda, Aduloju, Ogundare, and Talabi ( 2015) also reported that plots treated with combined application of poultry manure (2.5 t ha −1 ) mixed with 30 kg N ha −1 and foliar fertilizer commenced tasselling earlier at 38 days after planting while late (47 days) tasselling was recorded from the control. The above finding was in harmony with Bekele, Kibret, Bedadi, Balemi, and Yli-Halla (2018) who reported, the combined application of vermicompost, mineral P and lime significantly speeded up tasseling of maize. Early (102) days to tasseling were recorded with the application of lime, vermicompost, and mineral P fertilizer at the rate of 4 t ha −1 , 5 t ha −1 , and 40 kg ha −1 , respectively.…”
Section: Phenological Parameters Days To 50% Tasselingsupporting
confidence: 87%
“…In accordance with Bekele et al (2018), physiological maturity was significantly prolonged by applications of lime, vermicompost, and chemical P fertilizer. Application of the highest rates of all the three factors (lime = 4 t CaCO 3 , VC = 5 t and P = 40 kg ha −1 ) prolonged (75 days) maturity of maize by as much as 17 days compared to the control.…”
Section: Days To 90% Physiological Maturitymentioning
confidence: 61%
See 1 more Smart Citation
“…These acid soils are instead characterized by excess Al 3+ and H + which inhibit plant root development and the absorption of essential plant nutrients (Brady and weil 2014). Several factors are at the origin of soil acidity amongst which the nature of the parent rock, climate, vegetation, farming methods (slash and burn, excessive use of acidic fertilizers, etc) (Soltner 1988 Bekele et al 2018). In Cameroon, like most African Countries, demographic pressure on land has stirred counter season farming and fallow time reduction .…”
Section: Introductionmentioning
confidence: 99%
“…The aluminium becomes toxic and can strongly compromise productivity (Ibrahim et al 2012). Thus, continuous soil degradation is a constant preoccupation in Sub-Saharan Africa (Bindzi 1987;Ambassa-Kiki et al 2002;Bekele et al 2018). To maintain continuous crop production, the control of soil acidity is indispensable.…”
Section: Introductionmentioning
confidence: 99%